KINERJA SEKSI KESEHATAN IBU DAN ANAK DINAS KESEHATAN KOTA SEMARANG PADA PROGRAM SAYANGI DAMPINGI IBU DAN ANAK (SAN-PIISAN) - Sattar Ikhsan, Ghazan; Suwitri, Sri; Afrizal, Teuku (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
This research explains the performance of the Maternal and Child Health Section of the Semarang City Health Service. Performance is an achievement that has been made by each member of the organization in carrying out the tasks assigned to him and is based on experience, hard work and ability as well as good time management. Optimal organizational performance will accelerate the achievement of organizational targets. This research aims to analyze the performance of the Semarang City Health Service in the SAN-PIISAN program as well as supporting and inhibiting factors in the performance of the Semarang City Health Service. A qualitative descriptive approach was used with the case study method to describe the performance of the relevant organization, namely the Semarang City Health Service. In analyzing performance, researchers used the duties and functions of the Semarang DKK Maternal and Child Health Section and in analyzing factors used theories from Agus Dwiyanto and Kumorotomo which were combined into productivity, service quality, effectiveness and efficiency. The research results show that the Semarang City Health Service has carried out its duties and functions in accordance with Semarang Mayor Regulation No. 93 of 2021. Supporting factors for the performance of DKK Semarang in the SAN-PIISAN program are effectiveness and efficiency. Meanwhile, the inhibiting factors are productivity and service quality.